A qualitative process analysis of daily contact testing as an alternative to self-isolation following close contact with a confirmed carrier of SARS-CoV-2 - Sarah Denford; Alex F. Martin; Lauren Towler; Fiona Mowbray; Rosie Essery; Rachael Bloomer; Derren Ready; Nicola Love; Richard Amlôt; Isabel Oliver; G James Rubin; Lucy Yardley (BMC, 2022)
Abstract Background In July 2021, a randomised controlled trial was conducted to compare the effect on SARS-CoV-2 transmission of seven days of Daily Contact Testing (DCT) using Lateral Flow Test (LFT) and two Polymerase Chain Reaction (PCR) tests as an alternative to 10 days of standard self-isolation with one PCR, following close contact with a SARS-CoV-2 carrier. In this qualitative study, we used a nested process evaluation to aid interpretation of the trial and provide insight into factors influencing use of tests, understanding of test results, and how tests were used to inform behavioural decisions. Methods Interviews were conducted with 60 participants (42 randomised to DCT and 18 randomised to self-isolation) who had been in close contact with a confirmed SARS-CoV-2 carrier and had consented to take part in the trial. Results Data were organised into three overarching themes: (1) assessing the risks and benefits of DCT (2) use of testing during the study period and (3) future use of testing. Attitudes toward DCT as an alternative to self-isolation and behaviour during the testing period appeared to be informed by an assessment of the associated risks and benefits. Participants reported how important it was for them to avoid isolation, how necessary self-isolation was considered to be, and the ability of LFTs to detect infection. Behaviour during the testing period was modified to reduce risks and harms as much as possible. Testing was considered a potential compromise, reducing both risk of transmission and the negative impact of self-isolation, and was regarded as a way to return to normal. Conclusion Participants in this study viewed DCT as a sensible, feasible, and welcome means of avoiding unnecessary self-isolation. Although negative LFTs provided reassurance, most people still restricted their activity as recommended. DCT was also highly valued by those in vulnerable households as a means of providing reassurance of the absence of infection and as an important means of detecting infection and prompting self-isolation when necessary.